2016
DOI: 10.1039/c6cy00750c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of Pt38 in the oxygen reduction reaction from first-principles simulations

Abstract: The activity of a truncated octahedral Pt 38 clusters as a catalyst in the Oxygen Reduction Reaction (ORR) is investigated via first-principles simulations. Three catalytic steps: O 2 dissociation (O 2ads → 2 O ads ), O hydration (O ads + H 2 O ads → 2 OH ads ), and H 2 O formation (OH ads + H ads → H 2 O ads ) are considered, in which all reactant species are co-adsorbed on the Pt 38 cluster according to aLangmuir-Hinshelwood mechanism. The minimum structures and saddle points for these different steps are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Applications of condensed-matter continuum approaches in electro-chemistry and electro-catalysis in wet environments are among the main purposes that have driven these recent developments. [29,34,105,[107][108][109][110][113][114][115][116][117][118][119][120][121][122] There are different simulation strategies of increasing complexity that can be attempted and that could take substantial advantage from the use of continuum embedding techniques.…”
Section: Modeling Electro-chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of condensed-matter continuum approaches in electro-chemistry and electro-catalysis in wet environments are among the main purposes that have driven these recent developments. [29,34,105,[107][108][109][110][113][114][115][116][117][118][119][120][121][122] There are different simulation strategies of increasing complexity that can be attempted and that could take substantial advantage from the use of continuum embedding techniques.…”
Section: Modeling Electro-chemistrymentioning
confidence: 99%
“…As an example, Fortunelli et al showed that tuning the dielectric screening of the wet environment can increase by more than one order of magnitude the catalytic reactivity of Pt for the oxygen reduction reaction. [105,106,118] Similarly, the use of the computational hydrogen electrode technique may also take advantage of simulations in continuum environments.…”
Section: Modeling Electro-chemistrymentioning
confidence: 99%
“…The ORR activity of truncated octahedral Pt 38 clusters as a catalyst was investigated via first-principles simulations by Fortunelli's group. For Pt 38 clusters, the rate-determining step is the H 2 O formation, while for an extended surface such as the Pt (111) crystal plane, the O hydration is actually the overall reaction barrier [79]. Recently, Nigam et al carried out density function theory (DFT) calculations to examine the viability of alumina-supported Pt clusters (Pt n @Al 2 O 3 , n = 1-7, 10) as ORR electrocatalysts [80].…”
Section: Pt Clusters For Orrmentioning
confidence: 99%
“…To this end, we exploit and further develop the self-consistent continuum solvation (SCCS) approach proposed by Andreussi et al 27 to simulate semiconductor electrodes under applied voltage in electrolytic media. While this method has been successful in modeling metal electrodes, [28][29][30][31][32] no previous study has focused on describing band bending at semiconductor electrodes using a self-consistent continuum solvation approach. To illustrate band bending, the electrostatic profile of a semiconductor-electrolyte interface is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%